Peningkatan Tata Kelola dan Promosi Aneka Snack untuk Memperluas Pangsa Pasar Mancanegara - Nuur Rasyid, Haryadi Arief; Azis, Zuhdan (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2017)
Nowdays, snack products have new creations with started to be widely available. However, it is produced by micro, small and medium enterprises (UMKM), of course also experience constraints as MSME in general is not profes-sional yet did by the people and can not produce continuously. It is a small business, the production aspect of UMKM also uses simple methods and technology and still uses simple management as well. SMEs that move in the fulfillment of culinary tourism also has constraints and has characteristics sebagaiman above. Culinary business that seeks to support tourism include eel products/fried catfish crispy and seaweed. Both of these efforts are done by young people who are creative and have a willingness to go forward developing the business. For catfish fried crispy is done by Noviani brass with trademark â€œSari Rasaâ€ while for various snack that comes from seaweed developed by Br. Stenley Avanda with brand â€œPandaâ€. Once identified through observation and interviews it can be seen that the problems that are still faced include: 1) not understood yet how to market products to foreign tourists, 2)Â  not to implementation yet of professional governance and administration, including the absence of a good business plan, and regular organizational systems; 3) unavailability of English-speaking product packaging; 4) lack of promotion media using the internet; 5) the need for more intensive management assistance to penetrate the wider market. From these problems, efforts have been made to overcome them through activities such as the understanding of export management or foreign tourism through applicative training, product promotion by using English packaging, making brochures with english language and making english-language website. From a series of activities, both partners benefit from increased understanding of product sales to foreign tourists, and can take advantage of promotional media in accordance with the needs of foreign tourists.Â Keywords: Governance, promotion, various snacks.